THE IMPACT OF CENTRAL BANK DIGITAL CURRENCY IMPLEMENTATION ON THE MONETARY TRANSMISSION MECHANISM (Symposium on Natural and Applied Sciences, 2026)
The rapid digitalization of financial systems has prompted central banks worldwide to explore the introduction of Central Bank Digital Currency (CBDC) as a new form of sovereign money. This study examines the impact of CBDC implementation on the monetary transmission mechanism, focusing on its implications for interest rate channels, credit channels, expectations management, and financial stability. The research analyzes theoretical frameworks, global pilot experiences, and potential macroeconomic outcomes associated with CBDC adoption. Findings suggest that CBDC can enhance the efficiency, speed, and transparency of monetary policy transmission while introducing new risks related to banking sector disintermediation and financial stability. The paper concludes with policy recommendations for optimizing CBDC design to strengthen monetary policy effectiveness.
Keywords: Central Bank Digital Currency, Monetary Policy, Transmission Mechanism, Digital Finance, Interest Rate Channel, Financial Stability, Central Banking, Monetary Innovation.